Applying GIS and Markov chain in establishing the land use change map and forecasting land use changes in Thach That district, Hanoi city - Thi Oanh, Nguyen; Thi Dinh, Ngo; Nhat Anh, Be (Journal of Forestry Science and Technology, 2024)
The study applied GIS and Markov chains to assess land use changes in the period 2015-2020 and forecast land use change trends in Thach That district, Hanoi city until 2030. Using two maps of the land use status quo map in 2015 and 2020 of Thach That district and 2 period land statistics, the research result has established a land use change map in Thach That district for the period 2015 - 2020 for 16 types of land with a land change rate of 9.63% of the total natural area. During this period, the land types that tend to increase are Perennial crop land; Special-use Forest land; Aquaculture land; Other agricultural land; Residential land; Special-use land; Land for religious establishments; Land for beliefs establishments and Specialized water surfaces with an increased rate of 0.05-2.28%. In contrast, land types with a decreasing trend are Annual crop land; Production Forest land; Protective Forest land; Cemetery land, cemetery, funeral home, crematorium; Land of rivers, streams, canals and streams; Other non-agricultural land, and Unused land which decreased at a rate of 0.02-2.34%. It is forecast that by 2030, agricultural land will have 10,271.28 hectares (accounting for 54.90%), non-agricultural land will have 8,432.22 hectares (accounting for 45.07%), unused land will have 4.76 hectares (accounting for 0.03%). Performing a T-Test (Paired two sample for Means) between the area from the forecast and the planned area until 2030 shows that ρ = 0.979 > 0.05. Thus, it proves that the results of forecasting land use changes to 2030 using the Markov chain compared to the land use planning plan of Thach That district do not have too big a difference. The results of assessing land use changes and making forecasts of land change trends in the Thach That district contribute to helping policymakers have an objective view of land-use planning and economic development sustainably.